Transnational families : ethnicities, identities and social capital - Reynolds, Tracey; Zontini, Elisabetta; Solomos, John; Goulbourne, Harry (Relationships and resources (Routledge), 2011)
Presents an overview of the emergence of understandings of ethnicities, identities and family forms across a number of ethnic groups, family types, and national boundaries